2018
DOI: 10.4103/sni.sni_441_17
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cervical radiculopathy: A review of the evolution and economics

Abstract: Background:The surgical treatment of cervical radiculopathy has centered around anterior cervical discectomy and fusion (ACDF). Alternatively, the posterior cervical laminoforaminotomy/microdiscectomy (PCF/PCM), which results in comparable outcomes and is more cost-effective, has been underutilized.Methods:Here, we compared the direct/indirect costs, reoperation rates, and outcome for ACDF and PCF vs. PCM using PubMed, Medline, and Embase databases.Results:There were no significant differences between the re-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…The ACDF is the most commonly performed cervical spine procedure although previously published clinical trials have demonstrated that this procedure is associated with higher rates of complications than posterior cervical fusion. 6,7,20,21 There has been limited research into identifying, quantifying, and improving outcomes after posterior cervical fusions. DJK is one of the complications of posterior cervical fusion that is not well investigated because there are only a handful of publications focused on this complication.…”
Section: Discussionmentioning
confidence: 99%
“…The ACDF is the most commonly performed cervical spine procedure although previously published clinical trials have demonstrated that this procedure is associated with higher rates of complications than posterior cervical fusion. 6,7,20,21 There has been limited research into identifying, quantifying, and improving outcomes after posterior cervical fusions. DJK is one of the complications of posterior cervical fusion that is not well investigated because there are only a handful of publications focused on this complication.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of cervical radiculopathy occurs at an incidence rate of approximately 85 persons per 100,000. (2) The most common presentation of herniated cervical disc is radicular pain noticed upon awakening in the morning. (3) The diagnosis of radiculopathy is based on a detailed history taking and a thorough neurological examination.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies demonstrated reduced costs for variants of CLF (i.e..., open CLF, PCF/CPM, MICLF) vs. ACDF when addressing lateral cervical pathology [ Table 1 ]. [ 2 , 6 , 7 ] For 101 patients, Mansfield et al . (2014) compared the 3-year perioperative costs for 1-level ACDF vs. MICLF; average ACDF (largely implants) cost $8192 vs. $4320 for MICLF, but outcomes were comparable for both groups [ Table 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cervical laminoforaminotomy (CLF), whether performed open, minimally invasively (MI), or microendoscopically (ME) for lateral/foraminal cervical disc disease, are safer than anterior cervical diskectomy/fusion (ACDF) [Table 1]. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Notably, ACDF risks uniquely include, carotid artery or jugular vein injuries, esophageal tears, dysphagia, tracheal injuries, and recurrent laryngeal nerve injuries not posed by CLF. Further, CLF vs. ACDF offer marked reductions in the frequency of vertebral artery injuries, cord/nerve root deficits, spinal instability, dural tears (DT), tissue damage, operative time, estimated blood loss (EBL), adjacent segment disease, length of stay, and cost.…”
Section: Introductionmentioning
confidence: 99%